Integrated in silico techniques for mechanism studies of antiviral and antidiabetic compounds / Diyana Mohd Isa - Diyana , Mohd Isa (2020)

(untitled)
Discovery and development of drug is an iterative process that involves identification of target and leads discovery, lead optimization and pre-clinical of biological profile and is continued until the drugs are eligible to be tested in the clinical phase. Computer-aided drug design (CADD) is an efficient way to overcome the demands of cost, time consumption and drug validation. CADD utilizes in silico technique approaches such as molecular docking to understand their binding pattern and affinity with the target protein and molecular dynamic (MD) simulations to provide an atomic view of the dynamic behavior and stability of bioactive compound inside the target protein binding site in the aqueous solvent over a reasonable time scales. Thus, these computational techniques were able to accelerate and facilitate the drug discovery process in finding potential therapeutics lead. In this study, both methods were utilized to determine the key interaction that contributed to the optimal binding energy of antiviral and antidiabetic bioactive compounds. All compounds that were tested in in-vitro experiments gave a significant correlation with the computational calculation. Several residues were identified as key residues that provide significant information in improving and developing the compounds to be more potent towards the target or disease.